Effect of endosomal acidification on small ion transport through the anthrax toxin PA63 channel. Issue 21 (19th October 2017) - Kalu, Nnanya; Alcaraz, Antonio; Yamini, Goli; Momben Abolfath, Sanaz; Lucas, Laura; Kenney, Clare; Aguilella, Vicente M.; Nestorovich, Ekaterina M.
Abstract : Tight regulation of pH is critical for the structure and function of cells and organelles. The pH environment changes dramatically along the endocytic pathway, an internalization transport process that is 'hijacked' by many intracellularly active bacterial exotoxins, including the anthrax toxin. Here, we investigate the role of pH on single‐channel properties of the anthrax toxin protective antigen (PA63 ). Using conductance and current noise analysis, blocker binding, ion selectivity, and poly(ethylene glycol) partitioning measurements, we show that the channel exists in two different open states ('maximum' and 'main') at pH ≥ 5.5, while only a maximum conductance state is detected at pH < 5.5. We describe two substantially distinct patterns of PA63 conductance dependence on KCl concentration uncovered at pH 6.5 and 4.5. Abstract :